Examining the utility and accuracy of the interRAI emergency department screener in identifying high-risk older emergency department patients: a Canadian multiprovince prospective cohort study - Mowbray, Fabrice I. (2023)
We set out to determine the accuracy of the interRAI Emergency Department (ED) Screener in predicting the need for detailed geriatric assessment in the ED. Our secondary objective was to determine the discriminative ability of the interRAI ED Screener for predicting the odds of discharge home and extended ED length of stay (>24 hours).